Pruebas y Evaluación del protocolo IPv6 mediante la configuración de un servidor Proxy en Linux Centos 5.1 en uno de los laboratorios de la Universidad Técnica de Cotopaxi. - Iza Almachi, Deysi Silvana (2008)
The admition of the new technologies is not always regulated process, taking account every institution is obligated to use the technologies as a result of the investigation or for constant updates. The new version of the Protocol (IPv6), is a new technology that is boomingg, therefore this thesis proposes a guide for implementation in Double-Stack a service on the Internet, thus people can do test and evaluations of that protocol, taking into account needs of hardware, software, human resource, priorizing services, for purposes of the imminent transition could be as simple and as quickly as possible.